Doing business after Brexit : a practical guide to the legal changes - Wong, Helen (London [England] : Bloomsbury Professional, 2022)
"On 31st December 2020, the Brexit transition period ended and the new EU-UK partnership began. The second edition discusses the new EU-UK partnership, and the related agreements, looking at the effect these will have on businesses trading with the EU. The book then looks at each area pertinent to running a business and looks at the related advantages and disadvantages that arise from Brexit, e.g. the Brexit Trade and Cooperation Agreement, a new points-based immigration system, and customs and VAT rules on imports and exports."--
Part I Impact of Brexit Introduction -- Chapter 1 What is Brexit? -- Chapter 2 Economic impact and manufacturing -- Chapter 3 A legal contingency plan for Brexit -- Chapter 4 Tax (including VAT) -- Chapter 5 Financial services -- Chapter 6 Commercial contracts -- Chapter 7 Construction -- Chapter 8 Immigration -- Chapter 9 Commercial disputes -- Chapter 10 IP and data protection -- Chapter 11 Technology -- Chapter 12 Employment -- Chapter 13 Insolvency -- Part II Thought Leadership by Inspirational Leaders
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily.
Mode of access: World Wide Web.
Keywords: Commercial law -- Great Britain; Commercial law -- European Union countries; Great Britain -- Commercial policy; European Union countries -- Commercial policy; Electronic books